2021
DOI: 10.1177/0310057x20976655
|View full text |Cite
|
Sign up to set email alerts
|

Applications of 3D printing in critical care medicine: A scoping review

Abstract: Although a wide range of medical applications for three-dimensional printing technology have been recognised, little has been described about its utility in critical care medicine. The aim of this review was to identify three-dimensional printing applications related to critical care practice. A scoping review of the literature was conducted via a systematic search of three databases. A priori specified themes included airway management, procedural support, and simulation and medical education. The search iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(119 reference statements)
0
3
0
Order By: Relevance
“…In an era of technological progress, 3D models have emerged as potent tools for augmenting neurosurgical training [ 8 , 9 , 10 ]. They furnish detailed spatial awareness essential for surgical strategizing and execution, alongside facilitating practical simulations [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an era of technological progress, 3D models have emerged as potent tools for augmenting neurosurgical training [ 8 , 9 , 10 ]. They furnish detailed spatial awareness essential for surgical strategizing and execution, alongside facilitating practical simulations [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study involving four medical students and two instructors examined and proved the usability of 3D-printed stethoscopes in auscultation training, in which they simulated mitral stenosis, mitral regurgitation, and aortic stenosis [ 24 ]. Supraglottic airway management devices have been successfully developed and tested on Thiel embalmed bodies [ 25 ]; however, no previous work has reported the use of 3D printing for manufacturing MAYO tubes [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although 3D printing technology has been used in almost all fields of medicine and the vast majority of medical instruments have been manufactured and tested in international studies, we did not find previous studies which aimed to critically evaluate 3D printed stethoscopes or MAYO tubes in real or simulated medical environments, involving a significant number of participants. In addition, a recent review indicated that 3D printing in critical care settings is strongly under-researched and under-utilized [ 26 ].…”
Section: Introductionmentioning
confidence: 99%